PENERAPAN SMART BOX HYBRID DALAM MENINGKATKAN KEMANDIRIAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS IV - Indriyana Savitri Kapu; Razak Umar; Zohrawati Hiola (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to analyze the level of understanding, describe the application, determine the level of learning independence of fourth grade elementary school students on the material of Energy Changes before the application of Smart Box Hybrid teaching aids. This type of research is classroom action research. The subjects of this study were the homeroom teacher and the Science Teacher. The object of this study was students in the fourth grade Science subject at MIN 2 Gorontalo Regency consisting of 30 students in the Science subject of fourth grade at MIN 2 Gorontalo Regency consisting of 16 male and 14 female students. The data analysis techniques used in this study were analysis of test results and analysis of observation results. Based on the results of the study, it can be concluded that the application of Smart Box Hybrid on the material of energy changes provides a more interactive, interesting, and meaningful learning experience for students. This media combines visual, digital, and direct activity elements so that students are more active in participating in Science learning. After the application of Smart Box Hybrid, student independence has increased. This can be seen in the increase in completeness from the pre-cycle by 26%, increasing in cycle I to 36%, and in cycle II increasing to 90%. Thus, students' learning independence, which includes understanding the material on Energy Change, has increased in a better direction with the implementation of the Smart Box Hybrid.